Designing a Green Chemistry-Based Practical Guide: Enhancing Learning on Reaction Rates and Chemical Equilibrium - Afriani, Hana Nazelia; Widodo, Agus (Journal of Chemical Learning Innovation, 2025)
Purpose of the study: This study aims to determine the characteristics and quality of the green chemistry-based chemical reaction rate and equilibrium laboratory manual. Methodology: The research employed a modified 4-D development model (define, design, develop) to create a green chemistry-based practical manual. Initial stages involved analyzing student needs and curriculum compatibility. The manual was validated by experts and refined through student trials. Data were gathered via questionnaires assessing feasibility and quality, yielding a manual designed to enhance learning and environmental consciousness. Main Findings: The validation results by material experts showed that the developed practical manual was in the very good category with a percentage of 84.38%. While the validation results by media experts obtained a very good category with a percentage of 91% and students gave responses to the practical manual showing a very good category with a percentage of 88.2%. Novelty/Originality of this study: This study introduces a green chemistry-based practical guidebook for reaction rates and chemical equilibrium, emphasizing environmentally friendly practices. Unlike conventional manuals, it integrates sustainable materials and safety-focused procedures. By addressing gaps in practical resources and promoting ecological awareness, this research advances chemistry education by aligning hands-on learning with principles of sustainability, benefiting educators and students alike